Integrating Islamic Values into STEM Education: Perspectives From In-Service and Pre-Service Early Childhood Educators (THUFULA, 2024)
This study investigates the perceptions of in-service and pre-service early childhood educators regarding the integration of Islamic values into STEM (Science, Technology, Engineering, Mathematics) education and explores the potential development of these values within this framework. Utilizing a qualitative research design and purposive sampling, the study engaged 11 in-service teachers and 13 pre-service teachers from early childhood education (ECE) programs. Data were collected through semi-structured interviews and analysed using Braun and Clarke's six-phase approach to thematic analysis. This approach facilitated the identification of key themes, including the necessity of integrating Islamic values into STEM curricula, particularly the principles of Tawhid (Islamic monotheism), moral teachings, scholarly perspectives, and references from the Quran and Hadith. Participants emphasized the importance of Islamic symbols and identity in shaping STEM education for young children. The findings reveal diverse strategies for embedding these values within STEM subjects, utilizing pedagogical methods such as contextualized teaching, problem-based learning, and the incorporation of Islamic narratives. The analysis also highlighted challenges, such as limited resources and the need for educator training in integrating religious content into STEM. The study is limited by its small sample size and the specific cultural context of the participants, which may not fully represent the broader experiences of early childhood educators.